2019
DOI: 10.3233/jad-181238
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Recognition Memory Impairment and Glial Pathology in the hAPP-J20 Mouse Model of Alzheimer’s Disease

Abstract: The role of cellular changes in the neurovascular unit is increasingly being investigated to understand the pathogenesis of Alzheimer's disease. The aim of the current study was to determine the time course of recognition memory impairment in the J20 mouse model of AD, in relation to neuroinflammatory responses and the pathology of A .Male hAPP-J20 and wild-type mice were assessed at 3, 6, 9, and 12 months of age. The spontaneous object recognition (SOR) task provided a measure of memory, with assessment of bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 72 publications
3
36
0
Order By: Relevance
“…Using a chronic mouse preparation, previous research from our laboratory found no significant neurovascular deficits in the J20-hAPP mouse between 9-12m age 9 , despite neuroinflammation and memory deficits 5 . This is contrary to what other laboratories have shown with the J20-mouse at the same age 10-12 .…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…Using a chronic mouse preparation, previous research from our laboratory found no significant neurovascular deficits in the J20-hAPP mouse between 9-12m age 9 , despite neuroinflammation and memory deficits 5 . This is contrary to what other laboratories have shown with the J20-mouse at the same age 10-12 .…”
Section: Introductionmentioning
confidence: 73%
“…Amyloid plaques are a key pathological hallmark of AD and begin to form in the hippocampus in the J20-hAPP AD mouse at around 6m of age 5 . The progression of plaque pathology and subsequent inflammatory changes have been well characterised in the J20-AD mouse 5 .…”
Section: Amyloid-plaques Begin To Form In the Hippocampus Of 9m J20-amentioning
confidence: 99%
See 3 more Smart Citations